(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2023)
This article is about the benefits of swimming in maintaining human health. Swimming is very important for a person. They improve metabolism and blood circulation, strengthen the heart, blood vessels and lungs, develop muscles, relieve many diseases, have a positive effect on the psycho-emotional sphere, make a person slimmer and more beautiful, help us always be active, efficient, maintain interest in life until the end of our days .